(untitled) (Conference Zone, 2021)
The article focuses on the foundation of the digital economy and its key features in the tourism industry. Also, the application of digital technologies in the tourism and recreation industry, the creation of a digital online platform model "Tourism 4.0" with the widespread use of the achievements of the fourth industrial revolution.